DEM analysis on the triaxial behaviour of mudstone considering water disintegration. Issue 2 (October 2020) - Cao, Zhensheng; Jia, Tong; Zhang, Shaoqiang; Ouyang, Xun; Jiang, Chuanbin; Huang, Xin
Abstract: Mudstone is a typical type of soft rocks. It is stable and has high strength in its natural state. However, in presence of water the constituent minerals dissolve and the inter-grain bonds are weakened, which thereby greatly reduces the strength of mudstone. As one of the most prevailing geological formations in the southwestern China, understanding the mechanical behaviour of mudstone at different degrees of disintegration is of great importance to practical engineering. This paper presents a micro-mechanical analysis on the mechanical behaviour of mudstone at different degrees of disintegration using the discrete element method (DEM). The laboratory triaxial tests carried out on mudstone samples that have been merged in water for different time periods are simulated. The dissolution of minerals and weakening of bonds between grains are considered by reducing the selected input parameters of parallel bonds at random locations. Different degrees of disintegration are obtained by multiplying the selected input parameters of parallel bonds with different reducing factors. The stress-strain curves obtained using the proposed approach are in good agreements with the experimental data. The progressive failure mechanism of mudstone at different degrees of disintegration is investigated considering the characteristics of particle motion, contact variation and bond breakage. Micro-scale analysis shows that with the increasing of confining pressure, the fraction of shear breakage of parallel bonds increases but the declining rate of coordination number post peak decreases. These underlie the fundamental mechanism of the change of failure mode of mudstone from brittleness to ductileness. Regardless of its spatial locations, the majority of broken bonds for the disintegrated specimens are those bonds with reduced input parameters. And the fraction of altered bonds within the broken bonds increases with the increasing degree of disintegration. The current research provides insightful understanding of the fundamental behaviour of mudstone in the presence of water.